Geotechnical and geological investigation of slope stability of a section of road cut debris-slopes along NH-7, Uttarakhand, India - Gbétoglo Charles Komadja; Sarada Prasad Pradhan; Afolayan David Oluwasegun; Amulya Ratna Roul; Tido Tiwa Stanislas; Raoul Adéniyi Laïbi; Babatunde Adebayo; Azikiwe Peter Onwualu (Results in Engineering, 2021)
Slope stability is of significant importance for sustainable development in mining, civil-engineering, and urban planning. This paper attempted to assess the stability conditions of road cut debris slopes along the National Highway-7 (NH-7), Uttarakhand, India. The engineering parameters of the slope forming materials and other inputs used for slope stability analysis were evaluated based on different geotechnical tests such as direct shear strength, density analysis test, rock hardness tests, particle size analysis, Atterberg limits, and XRD analysis for the finer fraction of the slope materials. The slope stability was evaluated based on the limit equilibrium method (LEM) and finite-element methods based on strength reduction factor (FEM-SRF). The results showed that the slope materials are mainly comprised of well-graded sands, gravelly sands, with little or no plasticity and display no clay activity along with moderate cohesion (19.4–31.5 ​kPa) and internal friction angle (26.23° to 38.44°). The slope stability conditions based on LEM were consistent with the SRF-FEM and revealed that the slopes with the highest height and dip angle (L4 and L6) are critically stable with a strength reduction factor less than 1. Based on the above results, it is inferred that the slope geometry (overall slope angle and height) has the greatest effect on the stability conditions of the studied slopes rather than the activity of swelling clay minerals. Excavation at the crown part of the slope, installation of retaining and gabion walls along the toe and grass planting on the slope surface are possible stabilization measures to increase the stability of the slopes.